Exploring the psychological experience of novice nurses in stomatological hospitals in China: a phenomenological study - Jian Liu; Tiantian Lu; Yan Li; Hongyuan Dai; Li Li (BMC, 2024)
Abstract Background At the onset of their professional journey, novice nurses often undergo a multifaceted psychological experience as they transition from theoretical knowledge to clinical practice, potentially impacting their development of professional identity. However, limited research has been conducted on the psychological aspects pertaining to newly graduated nurses in stomatological hospitals in our country. Methods The phenomenological method and semi-structured interviews were used in this study, and the sample size of the interview was purposive sampling method. A semi-structured virtual interview was conducted with 21 new nurses in the department of stomatology. Colaizzi's analysis method was used to analyse the interview data. Results Based on Kramer's reality shock theoretical framework and analyzing interview data, this study extracted the psychological experiences of novice nurses during their first year of employment across four distinct stages. The four stages include: cheerful period, frustration period, adjustment period and competency period. Six themes and nine sub-themes were derived from the four period. Conclusion Due to the lack of professional knowledge, novice oral nurses will experience a series of complex positive and negative emotions at the beginning of their career. Through the research, the training of oral specialty theory, good psychological counseling and peer support can improve their participation in oral outpatient nursing. At the same time, the establishment of oral care quality assurance system and the improvement of oral care higher education in our country will become the focus of future research.